Innovating engineering education: Insights and lessons from the pandemic - Galvis-Lista, Ernesto; Gonzalez-Zabala, Mayda; Aguas-Nuñez, Roberto; Magana, Alejandra J; Bustamante-Martínez, Alexander (Journal of Education and e-Learning Research, 2025)
This study presents how engineering education evolved during the COVID-19 pandemic, offering a comprehensive scientometric analysis of research lessons and insights. By examining 933 relevant documents from Scopus published between 2020 and May 2023, the study identifies key shifts in focus, particularly the rapid adoption of online learning, distance education, and virtual teaching methods. The pandemic catalyzed a rapid transition to online and hybrid models, prompting innovative approaches to maintain educational quality and accessibility. The findings highlight how the pandemic accelerated the transition to digital and hybrid models, with "online learning," "distance education," and "e-learning" emerging as dominant themes indicating a major focus on remote education technologies. Despite challenges posed by remote settings, active and project-based learning remained essential, while psychological factors such as anxiety and depression underscored the importance of supportive learning environments. Global research collaboration flourished, with significant contributions from the United States, India, and Spain. A co-occurrence network analysis using VOSviewer reveals distinct research clusters, ranging from innovative teaching strategies to student mental health. This research article offers valuable insights into how the engineering education community adapted to unprecedented challenges during the pandemic, thereby providing recommendations for continuous innovation and the future of education after a pandemic.